Youth involvement in food preparation practices at home: A multi-method exploration of Latinx youth experiences and perspectives. (1st January 2020) - Martin Romero, Michelle Y.; Francis, Lori A.
Abstract: Youth are frequently involved in preparing meals for themselves and family members. Latinx youth may be more likely to be involved in food preparation compared to youth from other ethnic backgrounds. Involvement in food preparation has been linked to various positive health outcomes, such as better diet quality and higher self-esteem. However, little is known about how youth come to be involved in food preparation at home. In addition, previous research has failed to explore the perspectives of youth regarding their role in food preparation. The objective of the present study was to qualitatively explore the food preparation practices of youth from im/migrant Latinx families. A multi-method study consisting of participatory focus groups embedded within an ethnographic fieldwork period was conducted. Participatory focus groups with Latinx youth featured inclusive discussions and participatory techniques, such as draw-write-tell activities, photo-elicitation activities, a decision-making chart activity, and listing activities. Twenty-three youths ages 9–17 years participated in this study. A thematic analysis uncovered themes related to gender norm expectations, specific cooking skills bound by age and food type, and food preparation as an important household contribution. Findings illustrate the diverse experiences of Latinx youth in food preparation. The investigation of youth involvement in food preparation in the home environment may identify potential targets for obesity prevention and dietary health promotion.